Joy: the key to using media to move the needle on climate change - McCormick, Sabrina; Aldous, Annette; Yarbrough, Laurilee (Frontiers in Communication, 2024)
Introduction Reaching the public and engaging them in addressing climate change could be effectively motivated by film and television. Unfortunately, to-date, there is limited understanding regarding the mechanisms by which such media motivates behavior change to address climate. In this research, we sought to investigate how media exposure can motivate climate and environmentally-conscious behaviors by assessing how emotional responses of viewers or demographic characteristics affected subsequent behavior over weeks following exposure. Methods Participants (N = 352) were recruited online and randomly assigned to watch one of three video segments. In surveys before and 4 weeks after viewing, they reported on specific environmentally friendly actions they had taken in recent weeks. Using analysis of covariance (ANCOVA) adjusted for actions reported at baseline, we assessed whether the number of actions reported at follow-up differed by assigned video. Two ANCOVA models were pre-specified, one with video only and one with backwards selection on a list of demographic factors and emotions experienced while watching the videos. Results In the multivariable model, a higher level of action was associated with self-reported joy (p < 0.001) and fear (p < 0.01). Discussion These findings suggest that climate communication that engages audience members in a joyful emotional state or, to a lesser degree, a frightening experience may be most effective in increasing climate action.